Behaviour of radium, barium and the rare Earth elements in mid-Atlantic Ridge hydrothermal plumes - Selzer, S (2022)
Hydrothermal activity influences the distributions of trace elements and isotopes (TEIs) in the ocean, which in turn impacts our understanding of oceanic TEI-cycling and the utility of TEIs as geochemical tools to study a variety of fundamental ocean processes. New data- sets have emerged in recent years that demonstrate importance of hydrothermal plumes for mediating seawater chemistry. Such influences are driven in part by vent fluid emissions, as well as the scavenging effects that mineral precipitates impose on deep waters circulating over ridge systems. Ridges themselves may also be important for driving changes to the physical mixing of deep ocean waters and the dispersion of hydrothermal TEI signatures. Herein, this thesis explores the behaviours of three potentially powerful but hitherto poorly understood marine tracers in hydrothermal plumes: short-lived radio-isotopes radium-223 and radium- 224, the Eu anomaly (Eu*), and stable-isotopes barium-134 and barium-138. The data sets gathered for these studies derive from the sampling efforts along the Mid-Atlantic Ridge of GEOTRACES research cruise GA13 (JC156).